ANALISIS PERTUMBUHAN PELAYANAN FASILITAS PENDIDIKAN DAN KESEHATAN SESUDAH PEMEKARAN WILAYAH DI KECAMATAN SUNGAI BAHAR, PROVINSI JAMBI - Fenny Khofivah Rio Tobing; Rahel Situmorang; Herika M. Taki (Jurnal Lingkungan dan Kota, 2022)
Public service facilities are something that must be owned by a region in order to meet the basic needs of the daily activities of the people in the region. The availability of facilities in an area must be able to serve all activities in the area in order to improve the welfare of the people of the region. In the Regional Regulation of Muaro Jambi Regency No. 28 of 2009 concerning the establishment of the Districts of North Bahar, Sungai Bahar, and South Bahar explains that the division of territory is carried out in Sungai Bahar District in order to distribute facilities in the form of public services.. However, previous research explained that in 2015 after the regional division occurred, public facility services were still not evenly distributed, this was due to the low level of accessibility to facilities. The preparation of this report was carried out to analyze the growth of education and health facilities services that occurred in Sungai Bahar District before and after the expansion of the region. The research method used is a quantitative approach with descriptive and spatial analysis methods by mapping the distribution of public service facilities. The results of the analysis show that the growth of existing facilities is still not evenly distributed in all villages in the study location, measured by the need for availability and distance of affordability by using a reference from SNI 03-1733-2004 on procedures for planning housing environments in urban areas